Complicating canons: a critical literacy challenge to common core assessment. (21st February 2017) - Peel, Anne
Abstract: The widespread adoption of the Common Core State Standards in the US has prioritized rigorous reading of complex texts. The emphasis on text complexity has led to instructional and assessment materials that constrain critical literacy practices by emphasizing quantitative features of text, such as sentence length, and a static list of text exemplars over the critical lens of the reader. Assessments like the PARCC, designed to align with nationalized standards, create the impression that complex texts are synonymous with a homogenized literary canon. A critical analysis of the texts and questions included in the first administration of the PARCC assessment reveals that the PARCC excludes both diverse authors and critical, rigorous reading practices. Research demonstrates that many literary curricula and classroom activities are strongly influenced by standardized tests; therefore, I argue for a definition of rigorous reading that supports critical literacy pedagogy and opposes the narrowing definitions of rigor and complexity that are asserted by the Common Core and PARCC.